Pengaruh Pemberian Pupuk Organik Cair VIT-O Dan Media Tanam Terhadap Pertumbuhan Tanaman Cabai Rawit (Capsicum frutescens L.) - Waruwu, Derianus; Zulfida, Ida; Oesman, Roswita (UNIVERSITAS LABUHANBATU, 2023)
Chili is a seasonal fruit plant. It is very popular because of its spicy taste and has been a spice component in every dish for a long time. Almost every native Indonesian dish uses chilies. Furthermore, in 2019, cayenne pepper production was 49,246 tons. Furthermore, in 2020, cayenne pepper production will reach 61,160 tons. Furthermore, in 2021, production will reach 78,663 tons (BPS, 2022). Liquid organic fertilizer (POC) is a type of fertilizer made from organic materials. Organic fertilizer is the result of the decomposition of organic materials that are broken down (renovated) by microbes, the final result of which can provide the nutrients needed by plants for plant growth and development. Apart from using liquid organic fertilizer, the composition of soil media also plays an important role in increasing the growth of cayenne pepper plants. Planting media play an important role in supporting plant growth and providing a supply of nutrients for plants. This research used a randomized block factororial design that consisted of two factors, namely Factor 1. Various types of Vit-O liquid organic fertilizer concentrations consisting of 3 treatment levels, namely P0 = control (Vit-O liquid organic fertilizer), P1 = 100 ml liquid organic fertilizer Vit-O, and P2 = 200 ml liquid organic fertilizer Vit-O. Factor 2. Planting Media Composition M1 = 25% cowshed compost + 25% husk charcoal + 50% soil; M2 = 50% cowshed compost + 25% husk charcoal + 25% soil; M3 = 25% cowshed compost + 50% husk charcoal + 25% soil. Based on the research results, it can be concluded that: the single effect of giving Vit-O organic fertilizer is significantly different on plant height at the ages of 14 dap, 28 dap, and 35 dap, but is not significantly different at the ages of 21 dap, 42 dap, and 49 dap, and number of leaves at 14 days after; The single effect of differences in the composition of the planting media was significantly different on plant height at 14 dap, 28 dap, and 35 dap, and number of leaves at 14 dap and 21 dap, but was not significantly different on plant height at 21 dap, 42 dap, and 49 dap, and number of leaves at 28 days after planting, 35 days after planting, 42 days after planting, and 49 days after planting. The interaction effect of providing Vit-O organic fertilizer was significantly different on the production of sample plants in harvest I, but not significantly different in harvest II and harvest III, plant height, and number of leaves.